Nilai-Nilai Karakter dan Edukatif dalam Novel Orang-Orang Biasa Karya Andrea Hirata - Ulandari, Widia; Zasrianita, Fera; Wediasti, Welti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This research aims to describe the character and educational values in the novel Orang-orang Biasa by Andrea Hirata. This research is qualitative research. The method used in this research is descriptive. The data source is a novel with the title Orang-orang Biasa. The data obtained are in the form of words in the novel Orang-orang Biasa. The data collection technique is a note-taking technique because the data is in the form of text using data analysis techniques, informal presentation techniques based on this understanding, and the technique for presenting the results of data analysis in the form of character values, which include honesty, hard work, curiosity, likes to read, discipline, democracy, and love of the country. Analysis of educational values includes the values of love for the homeland, social care, love of peace, creativity, responsibility, and religion. The validity test uses the triangulation method. The results of the research show that the character elements of the characters consist of 7 data points from the analysis, the character values of the characters consist of 21 data points from the analysis, and the educational values consist of 15 data points from the analysis. In conclusion, the novel displays elements of character and educational values, such as honesty, hard work, religion, and social, with a total of 43 data points. Andrea Hirata packaged his disappointment with the world of education into a beautiful work, depicting the struggle of poor children to achieve their dreams. Keywords: Character, Educational Value, Character Value and Novel